USING TOTAL PHYSICAL RESPONSE METHOD FOR TEACHING ENGLISH TO EARLY CHILDHOOD - Karlina, Lisa (Universitas Muria Kudus, 2024)
Abstract: Choosing good method to make students learning English pleasant is a must. And Total Physical Response is one of an alternative good method for teaching English for young Learners. It can help young learners to memorize some commands or some vocabularies easily through use their physical movement. The purpose of this study is to analyze how teachers at TK Bintang Kudus teach English by using TPR method to their students. This research method uses qualitative descriptive design. Non-participant observation and interview are conducted as the data collection techniques. The results indicate that the teachers are more interested to implement TPR method in natural conditions both inside and outside of the classroom. The application of TPR method is also known that students not only respond with physical movement but also with verbal response. Interview data shows that teachers are more creative using the TPR method in interacting and communicating with the students. By using TPR method in daily activities in the school can make students more easily understand English.